Parent–Child Interaction Therapy With an Eight-Year-Old Child: A Case Study. Issue 1 (2nd January 2017) - Stokes, Jocelyn O.; Scudder, Ashley; Costello, Amanda H.; McNeil, Cheryl B.
ABSTRACT: We examined the outcome of Parent–Child Interaction Therapy (PCIT) with an 8-year-old child diagnosed with oppositional defiant disorder. We presented a theoretical basis for the use of PCIT with some children older than 6 and suggested clinical considerations as well as adaptations and modifications that may make PCIT applicable with this population. "Curtis, " a Caucasian male, made clinically significant improvements and no longer met diagnostic criteria for oppositional defiant disorder at posttreatment. His scores on the Child Behavior Checklist and Eyberg Child Behavior Inventory improved from the clinical range at pretreatment to within the normative range at posttreatment. Further research should examine the efficacy of PCIT with children older than 6 and the feasibility of the suggested adaptations and modifications for this population.